Programa Minha Casa Minha Vida : a gestão local na implantação das “habitações de interesse social” - Salvadeo, André Ricardo Arão (2015)
After a brief presentation about landmarks of housing in Brazil, this paper discusses the problems involving the design and implantation of PMCMV since the beginning of its implementation in 2009. At that time, in face of global crisis which was ranging, it was decided to launch the program before its complete enhancement, which may explain, in part, some of its shortcomings, particularly those which relate to aspects of their local management, in the context of municipalities. From a general presentation on the local management process operation (or implementation) of PMCMV, the focus is on the Gross Income I of the Program. From this, a question is raised: how were local actors organized and how did they put into practice the implementation of what had been designed at the Federal level? Aiming to answer this question, a case-study methodology was used, adopting as data collection exploratory interviews. The enterprises located in Bauru, in the Midwest of the state of Sao Paulo, were defined as samples of this study, limiting the interviews of representatives of the Executive and Legislative Power and employees connected to one of the Financial Authorities responsible for financing the PMCMV.